1993
DOI: 10.4141/cjps93-154
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthèse de la primevère (Primula obconica Hance): Effets du gaz carbonique et de l’éclairement

Abstract: Net CO2 exchange rates were measured on a 1 m2 crop of Primula obconica placed in a closed loop growing chamber as a function of irradiation and CO2 concentration. Greenhouse cultivation with CO2 enrichment (700 ppm) or without (350 ppm) had only very little effect on dry weight or on flowering rate and did not modify photosynthetic capacity of primrose. Productivity differences between horticultural techniques, such as supplemental lighting and/of CO2 enrichment, can be partly explained by study of photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The leaf carbon gain might thus be underestimated if the actual photosynthetic rate decreased with leaf aging. Other Primula species tend to exhibit large seasonal variation in photosynthetic capacity (Whale 1983;Combe et al 1993). However, since P. nutans can be considered as a simultaneous species, which all the leaves open as a flush during a short period, the carbon gain of individual ramets may not change so much because simultaneous leaf-open species tend to have a slow decrease of canopy photosynthesis during leaf aging (Kikuzawa 2003).…”
Section: Possible Contribution Of Phenology To Simulated Carbon Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaf carbon gain might thus be underestimated if the actual photosynthetic rate decreased with leaf aging. Other Primula species tend to exhibit large seasonal variation in photosynthetic capacity (Whale 1983;Combe et al 1993). However, since P. nutans can be considered as a simultaneous species, which all the leaves open as a flush during a short period, the carbon gain of individual ramets may not change so much because simultaneous leaf-open species tend to have a slow decrease of canopy photosynthesis during leaf aging (Kikuzawa 2003).…”
Section: Possible Contribution Of Phenology To Simulated Carbon Budgetmentioning
confidence: 99%
“…Even for the genus Primula there are only a few reported studies dealing with photosynthesis (Whale 1983;Combe et al 1993;Noda et al 2004Noda et al , 2007. Whale (1983) reported that the maximum photosynthetic rate of three Primula species declined steadily as the growing season advanced; this suggests the importance of early spring in the carbon economy of these species.…”
Section: Introductionmentioning
confidence: 96%